Reclaiming the social in socialization: A practice‐based understanding of newcomer adjustment. (2nd January 2020) - Harris, Lisa; Cooper‐Thomas, Helena; Smith, Peter; Smollan, Roy
Abstract: The socialization of an employee into a new role provides an opportunity for both the newcomer and the organization to maintain or improve current practices. In this paper, integrating ideas from a practice‐based perspective with the concept of sensemaking, we draw on the multiple perspectives provided by the newcomer and relevant colleagues to examine the socialization process. Using an inductive, qualitative approach analyzing 21 semi‐structured interviews in six organizations with four types of participant—newcomers, and their respective coworkers, managers, and human resource (HR) representatives—our findings shed light on how interactions between newcomers and these three types of insiders influence newcomers' enactment of organizational practices. Specifically, newcomers who received greater sensegiving from insiders had, in turn, more opportunity to sensetest their nascent understandings, and to sensemake using these inputs, leading to the replication of organizational practices. Conversely, newcomers with limited access to sensegiving were less able to sensetest, and instead relied more on previous experiences to make sense of their new environment, leading to the determination of practices. Newcomers with substantial prior work experience used this as a valuable input to sensemaking, allowing quasi‐replication and determination of organizational practices that were more likely to be accepted, although not always. Our findings highlight social aspects of socialization as integral to sensemaking processes and performance of practice. In order to optimize socialization, all stakeholders—newcomers, their colleagues, and HR—should consider how the fundamentally social nature of socialization might require each party to adapt their approach.